Drainage From Superior Vena Cava Improves Upper Body Oxygenation in Patients on Femoral Veno-Arterial Extracorporeal Membrane Oxygenation - Cai, Tong; Li, Chenglong; Xu, Bo; Wang, Liangshan; Du, Zhongtao; Hao, Xing; Guo, Dong; Xing, Zhichen; Jiang, Chunjing; Xin, Meng; Wang, Pengcheng; Fan, Qiushi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate the feasibility of drainage from the superior vena cava (SVC) to improve upper body oxygenation in patients with cardiogenic shock undergoing femoral veno-arterial extracorporeal membrane oxygenation (VA ECMO). Methods Seventeen adult patients receiving peripheral femoral VA ECMO for circulatory support were enrolled. The femoral drainage cannula was shifted three times (from the inferior vena cava (IVC) level to the SVC level and then the IVC level again), all under ultrasound guidance, at an interval of 15 minutes. The blood gas levels of the right radial artery (RA) and SVC and cerebral oxygen saturation (ScO2) were measured and compared. Results Fifteen patients (88.2%) were successfully weaned from ECMO, and 12 patients (70.6%) survived to discharge. The oxygen saturation (SO2) and oxygen partial pressure (PO2) of the RA (97.0 ± 3.5% to 98.3 ± 1.5%, P < 0.05, SO2; 127.4 ± 58.2 mmHg to 153.1 ± 67.8 mmHg, P < 0.05, PO2) and SVC (69.5 ± 9.0% to 75.7 ± 8.5%, P < 0.05, SO2; 38.5 ± 5.6 mmHg to 43.6 ± 6.4 mmHg, P < 0.05, PO2) were increased; ScO2 was also increased on both sides (left: 50.6 ± 8.6% to 55.0 ± 9.0%, P < 0.05; right: 48.7 ± 9.2% to 52.3 ± 9.8%, P < 0.05) when the femoral drainage cannula was shifted from the IVC level to the SVC level. When the femoral drainage cannula was shifted from SVC level to the IVC level again, the SO2 and PO2 of RA (98.3 ± 1.5% to 96.9 ± 3.2%, P <0.05, SO2; 153.1 ± 67.8 mmHg to 125.8 ± 63.3 mmHg, P <0.05, PO2) and SVC (75.7 ± 38.5% to 70.4 ± 7.6%, P <0.05, SO2; 43.6 ± 6.4 mmHg to 38.9 ± 4.5 mmHg, P <0.05, PO2) were decreased; ScO2 was also reduced on both sides (left: 55.0 ± 9.0% to 50.7 ± 8.2%, P < 0.05; right: 52.3 ± 9.8% to 48.7 ± 9.3%, P <0.05). Conclusion Drainage from the SVC by shifting the cannula upward could improve upper body oxygenation in patients with cardiogenic shock undergoing femoral VA ECMO. This cannulation strategy provides an alternative solution for differential hypoxia.